2014
DOI: 10.1371/journal.pone.0105028
|View full text |Cite
|
Sign up to set email alerts
|

Are Pharmaceuticals with Evolutionary Conserved Molecular Drug Targets More Potent to Cause Toxic Effects in Non-Target Organisms?

Abstract: The ubiquitous use of pharmaceuticals has resulted in a continuous discharge into wastewater and pharmaceuticals and their metabolites are found in the environment. Due to their design towards specific drug targets, pharmaceuticals may be therapeutically active already at low environmental concentrations. Several human drug targets are evolutionary conserved in aquatic organisms, raising concerns about effects of these pharmaceuticals in non-target organisms. In this study, we hypothesized that the toxicity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 52 publications
0
25
1
1
Order By: Relevance
“…This means that they may retain potential for bioactivity, even after deposition in the environment. In addition, the conservation of biochemical targets between humans and animals on the one hand, and non‐target organisms on the other, is likely to lead to non‐target effects . There is now significant concern internationally about the potential environmental implications of pharmaceuticals developed for humans and agricultural animals on non‐target species .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This means that they may retain potential for bioactivity, even after deposition in the environment. In addition, the conservation of biochemical targets between humans and animals on the one hand, and non‐target organisms on the other, is likely to lead to non‐target effects . There is now significant concern internationally about the potential environmental implications of pharmaceuticals developed for humans and agricultural animals on non‐target species .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the conservation of biochemical targets between humans and animals on the one hand, and non-target organisms on the other, is likely to lead to non-target effects. [2] There is now significant concern internationally about the potential environmental implications of pharmaceuticals developed for humans and agricultural animals on non-target species. [1] Filter-feeding aquatic organisms such as mussels are of special interest in this regard, since they filter estuarine water very efficiently and are known to be capable of bioconcentrating pharmaceuticals and other xenobiotics in their tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it was shown that pharmaceutical inhibition of calmodulin in D. magna led to a decrease in gene expression of a cuticle protein and vitellogenin (Furuhagen et al . ). Therefore, calmodulin may also be involved in signal pathways leading to altered abundances of cuticle proteins and vitellogenins found during predator exposure in our study.…”
Section: Discussionmentioning
confidence: 97%
“…To get further information on similar proteins, all significant protein sequences were blastp-searched against NCBI nr and swissprot databases using local standalone blast (Geer et al 2010).…”
Section: Bioinformatic Processingmentioning
confidence: 99%
“…(BAE et al, 2006;FREEMAN, 2007;LIU et al, 2007;KANHERE et al, 2014;DARSANA et al, 2015). O critério para a determinação da toxicidade aguda é a completa imobilização destes organismos após 24-48 horas de exposição à substância química em estudo (OECD Guideline 202, 2004 Sob condições adversas, as fêmeas podem responder com a produção de ovos de resistência, alterações no tempo de maturação reprodutiva e no número e tamanho de descendentes (COORS et al, 2004;PESTANA et al, 2010;FURUHAGEN et al, 2014;STANLEY et al, 2016;TRAUDT et al, 2016;BARATA et al, 2016). Do ponto de vista ecológico, alterações na reprodução podem acarretar em uma redução na taxa intrínseca de crescimento populacional dos organismos, a qual compromete a manutenção da população e eleva os riscos de extinções das populações locais (PESTANA et al, 2010).…”
Section: Biomarcadores Bioquímicosunclassified